Catalytic Properties of Polyampholytes, Polyampholyte-Metal Complexes, Polyampholyte-Metal Nanoparticles and Polyampholyte-Enzyme Conjugates: a Mini-Review - Kudaibergenov, S.E. (Karagandy University of the name of acad. E.A. Buketov, 2024)
This mini-review briefly discusses the catalytic properties of polyampholytes, polyampholyte-metal complexes, polyampholyte-metal nanoparticles and polyampholyte-catalase conjugates. Polyampholyte-based catalysts can mimic enzyme functions, facilitating reactions like hydrolysis, decomposition, hydrogenation, and oxidation of various substrates. Special focus is given to amphoteric hydrogels and cryogels that encapsulate metal nanoparticles or enzymes. These materials have demonstrated effectiveness in the hydrogenation of nitroaromatic compounds, oxidation of disulfide and aliphatic (or aromatic) alcohols under mild conditions, both in batch and flow-through reactors. Kinetic parameters, turnover numbers (TON), turnover frequencies (TOF), and activation energies are presented for a series of specific catalytic processes. Notably, flowthrough reactors exhibit significantly higher catalytic efficiency compared to batch reactors and can be used continuously for extended periods. Additionally, the review explores the potential of light-driven hydrogen and oxygen evolution reactions from water, facilitated by metal nanoparticles within amphoteric hydrogels in the presence of photosensitizers.
Keywords: Polyampholyte-metal complexes; polyampholyte-metal nanoparticles; polyampholyte-enzyme conjugates; catalysis; decomposition; hydrogenation; oxidation; water splitting